2016
DOI: 10.1002/biof.1296
|View full text |Cite
|
Sign up to set email alerts
|

Negletein as a neuroprotectant enhances the action of nerve growth factor and induces neurite outgrowth in PC12 cells

Abstract: Negletein has been shown to have therapeutic potential for inflammation-associated diseases, but its effect on neurite outgrowth is still unknown. The present study showed that negletein alone did not trigger PC12 cells to differentiate and extend neurites. When compared with the cells in the untreated control, a significant (P < 0.05) induction and a higher neurite outgrowth activity was observed when the cells were cotreated with negletein (10 µM) and a low dose of nerve growth factor (NGF; 5 ng/mL). The neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Some flavonoids, such as MOS and NEG, have been extensively studied mainly due to their promising antimicrobial, antitumor, and neuroprotective activity [20,23,32]. However, little information is available on other molecules, despite their structural relation to MOS and NEG; for example, few studies have been done on 5,6-dihydroxy-flavone 7 [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some flavonoids, such as MOS and NEG, have been extensively studied mainly due to their promising antimicrobial, antitumor, and neuroprotective activity [20,23,32]. However, little information is available on other molecules, despite their structural relation to MOS and NEG; for example, few studies have been done on 5,6-dihydroxy-flavone 7 [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The first two compounds are present in some plants used in folk medicine, such as Centaurea clementei (Boiss) (negletein) [21], and Desmos chinensis (Lour.) (mosloflavone) [22], their antioxidant characteristics are well known and several studies have found that they have beneficial effects on human health [23]. MOS and NEG were obtained by a simple synthesis starting from the 7-methyl ether of crysin, similarly to what was described in Righi et al [24].…”
Section: Introductionmentioning
confidence: 99%
“…PC12 cells originate from the pheochromocytoma of the rat adrenal medulla and are widely established as a neuronal model [18, 19] in differentiated [20, 21] or undifferentiated [22, 23] form.…”
Section: Introductionmentioning
confidence: 99%
“…The kinase c-Jun N-terminal kinase 1/2, downstream of ASK1, may phosphorylate and activate FoxO1 protein, resulting in cell apoptosis (41). On the other hand, Phan et al (42) had reported that negletein together with NGF enhanced the phosphorylation of AKT and CREB, helping to protect neurons from cell death and promoting neuritogenesis in serum-deprived PC12 cells. In the present study, the increased expression levels of ASK1 and FoxO1 were observed in RGCs exposed to 40, 60 and 80 mmHg HP.…”
Section: Discussionmentioning
confidence: 99%